IMPROVEMENT BONDING QUALITY OF SHOE USING QUALITY CONTROL CIRCLE - Meike Elsye Beatrix; Novera Elisa Triana (Universitas Mercu Buana, 2019)
Shoe industry development in the era of globalization is currently overgrowing. Therefore, every company should be able to compete strictly with other companies that produce the same products. Quality maintenance is having to be done by the company to survive in business competition. PT. ABC is a manufacturer of sports shoes. The company has a problem with bonding shoes not achieved company standard in the year 2017. This paper is focused on the improvement of bonding shoe quality by using a method of Quality Control Circle which applying quality control tools are like check sheet, Pareto diagram, fishbone diagram, and 5W + 1 H. Based on the research results obtained percentage improvements of quality bonding test of 21.15%. Cement stripping on the midsole is the most significant number of the bonding test failure in Laboratory that is as much as 26.33% or 218 prs from the total collapse of the overall bonding shoes. Based on the background, the purpose of this research is to find out the root causes of the failure of bonding test shoes. The limitations of this research are only improving processes in the department, which makes the bonding shoe quality does not achieve the company standard. After doing the analysis using the quality control tools and making the improvement process in the whole areas that the percentage of the bonding test cement stripping on midsole could be increased to 5.18%. Analysis of the results obtained by applying the method of Quality Control Circle is the improvement of the quality of the bonding shoe. So, the trust customers against the company may be obtained that would eventually increase the number of orders to the company.